2006
DOI: 10.1200/jco.2006.07.5499
|View full text |Cite
|
Sign up to set email alerts
|

Raf Kinase Inhibitor Protein Expression in a Survival Analysis of Colorectal Cancer Patients

Abstract: RKIP expression in primary CRCs correlates with overall and disease-free survival, and can be useful for identifying early-stage CRC patients at risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
176
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 38 publications
20
176
4
1
Order By: Relevance
“…On the molecular level, RKIP functions by inhibiting the proliferative and survival Raf-MEK-ERK and NF-kB signaling pathways (Chatterjee et al, 2004;Park et al, 2005). Consistent with its demonstrated inhibitory effect on Raf and NF-kB signaling, we and others have shown that the expression levels of RKIP are downregulated in a number of tumors, including highly metastatic prostate, breast and colon cancer, hepatocellular carcinoma, melanomas and insulinomas (Fu et al, 2003;Chatterjee et al, 2004;Schuierer et al, 2004Schuierer et al, , 2006Zhang et al, 2004;Hegan et al, 2005;Al-Mulla et al, 2006;Lee et al, 2006). The importance of RKIP in metastases was highlighted by the finding that restoration of RKIP expression inhibits prostate cancer metastasis in a murine model (Fu et al, 2003(Fu et al, , 2005.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…On the molecular level, RKIP functions by inhibiting the proliferative and survival Raf-MEK-ERK and NF-kB signaling pathways (Chatterjee et al, 2004;Park et al, 2005). Consistent with its demonstrated inhibitory effect on Raf and NF-kB signaling, we and others have shown that the expression levels of RKIP are downregulated in a number of tumors, including highly metastatic prostate, breast and colon cancer, hepatocellular carcinoma, melanomas and insulinomas (Fu et al, 2003;Chatterjee et al, 2004;Schuierer et al, 2004Schuierer et al, , 2006Zhang et al, 2004;Hegan et al, 2005;Al-Mulla et al, 2006;Lee et al, 2006). The importance of RKIP in metastases was highlighted by the finding that restoration of RKIP expression inhibits prostate cancer metastasis in a murine model (Fu et al, 2003(Fu et al, , 2005.…”
supporting
confidence: 61%
“…The importance of RKIP in metastases was highlighted by the finding that restoration of RKIP expression inhibits prostate cancer metastasis in a murine model (Fu et al, 2003(Fu et al, , 2005. More recent studies have shown that RKIP is also a good prognostic marker of the pathogenesis of human prostate cancer (Fu et al, 2005) and a prognostic indicator for overall survival and disease-free survival in colorectal cancer (Al-Mulla et al, 2006). Collectively, these studies suggest that RKIP is a novel cancer metastasis suppressor and an effector of signal transduction pathways leading to apoptosis.…”
mentioning
confidence: 99%
“…Previous studies have described low levels of RKIP in other metastatic tumors, such as breast and colorectal carcinoma (23,45), as well as in many other primary tumors, including GISTs (27), insulinoma (22), hepatocarcinoma (24), ovarian carcinoma (26), merckel cell carcinoma (16) and thyroid carcinoma (15), cutaneous squamous cell carcinoma (46) and nasopharyngeal carcinoma (17). Furthermore, loss of cytoplasmic RKIP has also been associated with poor prognosis in prostate, colorectal, GISTs and glial tumors (25,(27)(28)(29)(30).…”
Section: Univariate Analysis Multivariate Analysismentioning
confidence: 99%
“…In cancer, RKIP is considered to be a signal transduction modulator and a metastasis suppressor (14), and down regulated in several human tumors, mainly in highly metastatic carcinomas (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Noteworthy, RKIP has been shown to be a prognostic marker in prostate cancer, colorectal carcinomas, gliomas and GISTs (25,(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation